THE MEDIATING ROLE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND PSYCHOLOGICAL EMPOWERMENT: TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE - Syafitri, Sulistiani (Jurnal Mebis, 2024)
This study aims to investigate the mediating role of Organizational Citizenship Behavior and Psychological Empowerment in the relationship between Transformational Leadership, and their impact on Employee Performance at The State Electricity Company. The data collected for this research includes 272 employees based on the entire employee of The State Electricity Company who have a minimum of one year work experience and have direct supervisors and colleagues participating as research respondents. The study will be conducted using the structural equation modeling (SEM) method with the AMOS application